The Effectiveness of Policy Implementation for the Development of Disaster-Resilient Tourism by the Padang City Government - Ahmad, Taufani; Putera, Roni Ekha; Koeswara, Hendri (Pencerah, 2024)
This study aims to analyze the effectiveness of the implementation of disaster-resilient tourism development policies carried out by the Padang City Government. The research was conducted in 11 districts in Padang City, with informants being stakeholders who play a key role in the implementation of this policy, such as the Mayor of Padang, the Regional Secretary of Padang City, the Padang City Council, the Padang City Tourism Office, the Padang City BPBD, members of the Balawisata Padang, members of Pokdarwis Padang, the Board of the Disaster Risk Reduction Forum (FPRB) Padang, members of the Disaster Alert Group (KSB), as well as Non-Governmental Organizations involved in the implementation of this policy, such as the Tsunami Alert Community (Kogami) Padang, and the Disaster Alert Cadets (Tagana) Padang, Districts and Villages under the policy’s supervision, as well as the communities in the target areas of this policy.The research method used is descriptive qualitative, with informant selection using purposive sampling techniques, combining data from observations, interviews, and documentation, and interpreting both etic and emic data in an integrated manner. The results of this study conclude that overall, the implementation of the disaster-resilient tourism development policy by the Padang City Government has been carried out but is not yet effective. This is due to several factors, such as the lack of regulations and derivative documents that can serve as guidelines, which has caused stakeholders and the community to be hesitant and passive in implementing the policy. Furthermore, in terms of integration, the lack of communication and coordination between policy implementers at the city level and stakeholders at the district and village levels has resulted in a relationship pattern that does not align with what was initially planned. Regarding the adaptation instrument, the limited facilities and infrastructure owned by the village and district offices have caused the policy implementation to stagnate in these areas.